Dokumentation der Auftaktveranstaltung zur 2. Förderphase von ProDaZ - Büttner, Denise

Numerical analysis of partial differential equations on and of evolving surfaces - Kovács, Balázs

Discrete maximum principles for nonlinear elliptic finite element problems on surfaces with boundary - Karátson, János; Kovács, Balázs; Korotov, Sergey (IMA Journal of Numerical Analysis)
Abstract The maximum principle forms an important qualitative property of second-order elliptic equations; therefore, its discrete analogues, the so-called discrete maximum principles (DMPs), have drawn much attention owing to their role in reinforcing the qualitative reliability of the given numerical scheme. In this paper DMPs are established for nonlinear finite element problems on surfaces with boundary, corresponding to the classical pointwise maximum principles on Riemannian manifolds in the spirit of Pucci & Serrin (2007, The Maximum Principle. Springer). Various real-life examples illustrate the scope of the results.
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Discrete maximum principles for nonlinear elliptic finite element problems on surfaces with boundary - Karátson, János; Kovács, Balázs; Korotov, Sergey (IMA Journal of Numerical Analysis)
Abstract The maximum principle forms an important qualitative property of second-order elliptic equations; therefore, its discrete analogues, the so-called discrete maximum principles (DMPs), have drawn much attention owing to their role in reinforcing the qualitative reliability of the given numerical scheme. In this paper DMPs are established for nonlinear finite element problems on surfaces with boundary, corresponding to the classical pointwise maximum principles on Riemannian manifolds in the spirit of Pucci & Serrin (2007, The Maximum Principle. Springer). Various real-life examples illustrate the scope of the results.
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Linearly implicit full discretization of surface evolution - Kovács, Balázs; Lubich, Christian (Numerische Mathematik)
Keywords: Applied Mathematics; Computational Mathematics

Computing arbitrary Lagrangian Eulerian maps for evolving surfaces - Kovács, Balázs (Numerical Methods for Partial Differential Equations)
Keywords: Applied Mathematics; Computational Mathematics; Numerical Analysis; Analysis

Systematik zur integrativen Planung des Verhaltens selbstoptimierender Produktionssysteme - Köchling, Daniel

On period relations for automorphic 𝐿-functions I - Januszewski, Fabian (Transactions of the American Mathematical Society)
This paper is the first in a series of two dedicated to the study of period relations of the type <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="upper L left-parenthesis one half plus k comma normal upper Pi right-parenthesis element-of left-parenthesis 2 pi i right-parenthesis Superscript d dot k Baseline normal upper Omega Subscript left-parenthesis negative 1 right-parenthesis Sub Superscript k Subscript Baseline reverse-solidus bf upper Q left-parenthesis normal upper Pi right-parenthesis comma one half plus k critical comma"> L ( 1 2 + k , Π<!-- Π --> ) ∈<!-- ∈ --> ( 2 π<!-- π --> i ) d ⋅<!-- ⋅ --> k Ω<!-- Ω --> ( −<!-- − --> 1 ) k \bf Q ( Π<!-- Π --> ) , 1 2 + k critical , \begin{equation*} L\Big (\frac {1}{2}+k,Π \Big )\;\in \;(2π i)^{d· k}Ω _{(-1)^k}\textrm {\bf Q}(Π ),\quad \frac {1}{2}+k\;\text {critical}, \end{equation*} for certain automorphic representations Π<!-- Π --> Π of a reductive group G . G. In this paper we discuss the case <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="upper G equals normal upper G normal upper L left-parenthesis n plus 1 right-parenthesis times normal upper G normal upper L left-parenthesis n right-parenthesis period"> G = G L ( n + 1 ) ×<!-- × --> G L ( n ) . G=GL(n+1)× GL(n). The case G = G L ( 2 n ) G=GL(2n) is discussed in part two. Our method is representation theoretic and relies on the author’s recent results on global rational structures on automorphic representations. We show that the above period relations are intimately related to the field of definition of the global representation Π<!-- Π --> Π under consideration. The new period relations we prove are in accordance with Deligne’s Conjecture on special values of L L -functions, and the author expects this method to apply to other cases as well.
Keywords: Applied Mathematics; General Mathematics

In the Restaurant: From Michelin Stars to Fast Food; What Eating Out Tells Us About Who We Are - Ribbat, Christoph

Improper Signaling for OFDM Underlay Cognitive Radio Systems - Soleymani, Mohammad; Lameiro, Christian; Schreier, Peter J.; Santamaria, Ignacio (2018 IEEE Statistical Signal Processing Workshop (SSP))

Guter Raumlehreunterricht in der Volksschule nach dem Arbeitsschulprinzip am Beispiel von Ernst Heywang und Karl Pietzker - Werth, Gerda (Beiträge zum Mathematikunterricht)

"Im Streichen war sie hemmungslos" – Zur Rezeption Helene Bergs - Ricke, Anna (Erinnerung stiften: Helene Berg und das Erbe Alban Bergs)

Osterfestberechnung und Weltchronistik in den Reichen der Westgoten - Englisch, Brigitte (Proceedings of the 3rd International Conference on the Science of Computus in Ireland and Europe, Galway 16-18 July, 2010)

Restrukturierungen: operative und finanzielle Wertbeiträge. Eine Betrachtung vor dem Hintergrund der Entwicklungen bei thyssenkrupp - Sievers, Sönke; Sureth-Sloane, Caren; Uhde, André (Die Wirtschaftsprüfung)
Restrukturierungen werden sowohl durch die Digitalisierung, aber auch durch klassische Themen – beispielsweise die Notwendigkeit von Umsatz- und Kostensynergien in kompetitiven Märkten – verstärkt vorangetrieben. Dieser Beitrag beleuchtet vor allem die Motive und Folgen aus wissenschaftlicher Perspektive, indem großzahlige empirische Befunde zu den Themen Beschäftigung, Finanzkennzahlen und Kapitalerhöhungen sowie steuerliche Motive prägnant zusammengefasst und im Kontext des geplanten Joint Ventures von thyssenkrupp und Tata Steel diskutiert werden.

Restrukturierungen: operative und finanzielle Wertbeiträge. Eine Betrachtung vor dem Hintergrund der Entwicklungen bei thyssenkrupp - Sureth-Sloane, Caren; Sievers, Sönke; Uhde, André (Die Wirtschaftsprüfung)
Restrukturierungen werden sowohl durch die Digitalisierung, aber auch durch klassische Themen – beispielsweise die Notwendigkeit von Umsatz- und Kostensynergien in kompetitiven Märkten – verstärkt vorangetrieben. Dieser Beitrag beleuchtet vor allem die Motive und Folgen aus wissenschaftlicher Perspektive, indem großzahlige empirische Befunde zu den Themen Beschäftigung, Finanzkennzahlen und Kapitalerhöhungen sowie steuerliche Motive prägnant zusammengefasst und im Kontext des geplanten Joint Ventures von thyssenkrupp und Tata Steel diskutiert werden.

Restrukturierungen: operative und finanzielle Wertbeiträge. Eine Betrachtung vor dem Hintergrund der Entwicklungen bei thyssenkrupp - Sievers, Sönke; Sureth-Sloane, Caren; Uhde, André (Die Wirtschaftsprüfung)
Restrukturierungen werden sowohl durch die Digitalisierung, aber auch durch klassische Themen – beispielsweise die Notwendigkeit von Umsatz- und Kostensynergien in kompetitiven Märkten – verstärkt vorangetrieben. Dieser Beitrag beleuchtet vor allem die Motive und Folgen aus wissenschaftlicher Perspektive, indem großzahlige empirische Befunde zu den Themen Beschäftigung, Finanzkennzahlen und Kapitalerhöhungen sowie steuerliche Motive prägnant zusammengefasst und im Kontext des geplanten Joint Ventures von thyssenkrupp und Tata Steel diskutiert werden.

Present Research on Mathematics Textbooks and Teachers’ Resources in ICME-13: Conclusion and Perspectives - Rezat, Sebastian; Visnovska, Jana; Trouche, Luc; Qi, Chunxia; Fan, Lianghuo (Research on Mathematics Textbooks and Teachers’ Resources: Advances and Issues)

Textaufgaben verstehen. Lesen und Variieren komplexer Textaufgaben mit sprachlich-mathematischen Strategien. - Topalović, Elvira; Kuzminykh, Ksenia; Rezat, Sebastian (In: mathematik lehren)

Examining peer-interaction during individual work with a digital textbook in a primary mathematics classroom - Rezat, Sebastian; Häsel-Weide, Uta (PROCEEDINGS of the fith ERME TOPIC CONFERENCE (ETC 5) on Mathematics Education in the Digital Age (MEDA))

Theoretical frameworks for designing and analyzing language-responsive mathematics teaching–learning arrangements - Wessel, Lena; Erath, Kirstin (ZDM)
Keywords: General Mathematics; Education